The theory of reputation economy as a new paradigm for the study of the region economic potential - M. R. Safiullin; A. S. Grunichev; A. A. Abdukaeva (Вестник университета)
The modern economy with all the variety of its structural elements, which every year is increasingly immersed in a hyper-connected digital space, new conditions of institutional functioning caused by both a change in technological patterns and innovative forms of thinking, needs to adjust the basic, established principles and models of economic growth. If earlier the material productive factors was played a key role, today their importance is to some extent offset by the increasing role of non-material factors of production, the most important of which should include reputation capital. The purpose of the article is to comprehend and theoretically support this scientific problem. The need to revise some principles of building models of economic dynamics and strategic management of the region based on the use and revision of structural, logical and evolutionary views on the construction of this process is substantiated in the article. Based on the results of systematization of the evolution of methodological approaches to assessing the effectiveness of regional socio-economic development of territories / regions, the position is substantiated, according to which, in modern economic conditions, the effectiveness of territorial development should be based on research and strengthening of reputation capital.